Gastronomic Tourism Attractions in the Kapau Village, Agam Regency, West Sumatra - Sari, Putri Andan; Turgarini, Dewi; Handyastuti, Indriyani (Universitas Pendidikan Indonesia, 2019)
This research's aim is to find out the grand of gastronomy in Kapau , the components of gastronomy in Kapau, people 's contributions and government acts to preserve traditional gastronomy in Kapau, Agam , West Sumatra. Kapau, is a small region in West Sumatra that is known by fine traditional foods that have a unique taste on every food they are made. Therefore, Kapau is also known as a village that creates many expert chefs. To reach the aims written above, this research uses the mix method both qualitative and quantitative. Observation, questionnaire, interview and some documentary studies used to get the data. The result of this research is shows that Kapau Rice is a kind of traditional gastronomy that is very famous, not only among the Kapau citizens, but it is also known by the larger society outside. Regarding gastronomic tourist attractions in Kapau Village, Kapau rice has a good and unique taste and which cannot be found in other food. Gastronomy conservation has been done by government, chefs, and local leaders of the village by passing the cooking method from generation to generation. As a recommendation gastronomic travel pattern has been made in order to conserve traditional gastronomic in Kapau Village. Kapau rice consist of diverse Kapau traditional food such as Rendang, Gulai and Dendeng.